Conserving Biólogical Diversity in tbe Tropics: Tbe Role ofPrivate Nature Reserves in Costa Rica - Herzog, Patrick (Universidad de Costa Rica, 1998)
Conservation efforts to preserve biological diversity are often focused on the establishment of protected areas such as national parks, wildlife refuges and forest reserves (McNeely et al. 1990, WRI, mCN, UNEP 1992) under government control.